Characteristics and dynamics of malaria vectors around the Soum dam in Nanoro Health District, Burkina Faso - Hamidou Ilboudo; Elodie Doda Gricela Sanon; Domonbabele François de Sales Hien; Fadilah Traoré; Helle Hansson; Berenger Kabore; Marc Christian Tahita; Karim Derra; Eli Rouamba; Ismaïla Bouda; Toussaint Rouamba; Michael Alifrangis; et al. (PLoS ONE, 2026)
Malaria is endemic in Burkina Faso, with seasonal transmission during the rainy season. Environmental changes such as dam construction may influence mosquito ecology and malaria transmission; however, entomological data from this area remain limited. This study aimed to characterize malaria vector dynamics, including species composition, blood meal sources, and sporozoite infection rates, in five villages at varying distances from the Soum dam located in the Nanoro Health District catchment area in Burkina Faso. From March 2022 to February 2023, mosquitoes were collected monthly via pyrethrum spray catches (PSCs) targeting indoor resting vectors. Mosquitoes were identified morphologically via taxonomic keys. PCR analyses were performed to identify species within the Anopheles gambiae complex, determine blood meal sources, and assess Plasmodium falciparum infection. A total of 11,378 Anopheles mosquitoes were collected, including 3,432 males (30.1%) and 7,948 females (69.9%). An. gambiae s.l . was the most abundant species (86.5%), followed by An. funestus (10.6%). Within the An. gambiae complex, 91.5% were An. coluzzii , 8.3% An. arabiensis , and 0.2% An. gambiae sensu stricto . The vector density was highest in Soum (49.7%) and decreased with distance from the dam. The overall sporozoite rate was 6.2%, with higher rates in Seguedin (9.5%) and Soala (8.7%). Among the tested mosquitoes, 34.7% fed on humans, 14.2% on animals, and 23.6% on both. Anopheles coluzzii was the predominant vector and showed moderate anthropophilic behavior. Despite higher vector density near the dam, infection rates were greater in distant villages, highlighting the complexity of vector dynamics in dam-associated areas and the need for localized control strategies.